LEAF ANATOMY OF PANDANUS SPP. (PANDANACEAE) FROM SEBANGAU AND BUKIT BAKA-BUKIT RAYA NATIONAL PARK, KALIMANTAN, INDONESIA - Tihurua, Eka Fatmawati; Erlinawati, Ina (Research Center for Biology, 2014)
Cross sections of leaves of Pandanus spp. showed that their leaf anatomy is similar, whilst paradermal sections indicated that crystal numbers differ. Variation was found in the anticlinal epidermal cell walls, stomata, hypodermis, sclerenchyma, mesophyll and crystals, as discussed in this paper.